Assessment of Furcation Defects in Diabetic Patients with Chronic Periodontitis - An Institutional Based Retrospective Study - THIRUNAVAKARASU, RESHMA; S, BALAJI GANESH (The journal of contemporary issues in business and government, 2021)
Diabetes Mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia and disturbances of carbohydrate, fat and protein metabolism. Poorly controlled DM has been associated with increased susceptibility to oral infections including periodontal diseases. It is well documented that one of the main causes of diabetes mellitus is that it leads to periodontal destruction which eventually leads to furcation exposure. This leads to poor prognosis of the affected tooth. Thus the aim of this study is to determine the most common furcation site involved in patients with diabetes. Completed case sheets were collected from June 2019 to April 2020. Data was retrieved and evaluated by 2 reviewers. This university setting study involved 700 sample sizes. Data is tabulated the parameters which are age groups, gender, RBS value and furcation grade. Ranges of RBS values are from 150mg/dl to >551mg/dl. A total of 700 patients case sheets were evaluated and their periodontal status was evaluated. 500 molars were affected (3rd molars exempted). It was found that among all the age groups the most number of participants were seen in 41-60 years (66%). Majority of the affected molars has a grade II furcation involvement (45%). 35.40% had grade I furcation involvement followed by 15.60% of affected teeth with grade III furcation involvement and finally 4% had grade IV furcation involvement. Amongst the teeth with grade I and grade III it was found that 16 was the mostly affected. For grade II furcation involvement it was seen that 46 was mostly affected. Association between grade I, II and III furcation and age groups was statistically insignificant. Finally, 37 was the most affected among the teeth with grade IV furcation involvement. Association between grade IV furcation and age groups was statistically significant (p value=0.006) Thus we can conclude that diabetes mellitus is associated with periodontal disease and in this study it is evident that it involves the furcation area of molars. Diabetic patients are more prone to severe periodontitis with multiple furcation involvement.